2023
DOI: 10.3389/fped.2023.1259384
|View full text |Cite
|
Sign up to set email alerts
|

Impact of CytoSorb and CKRT on hemodynamics in pediatric patients with septic shock: the PedCyto study

Gabriella Bottari,
Isabella Guzzo,
Andrea Cappoli
et al.

Abstract: BackgroundThere is a lack of data to support the use of hemoadsorption in pediatric septic shock. The aim of our study was to assess the effectiveness and safety of CytoSorb therapy in this setting.MethodsPhase II interventional single arm pilot study in which 17 consecutive children admitted with septic shock who required continuous kidney replacement therapy (CKRT) and weighed ≥10 kg were included. A CytoSorb (CytoSorbents Inc, New Jersey, USA) hemoadsorption cartridge was added to the CKRT every 24 h for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The study protocol underwent review and approval by the local Ethics Committee in July 2019 (Ethics Committee Reference: N376). Informed written consent was obtained from the next of kin or legal guardian for each patient enrolled in the study (9).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study protocol underwent review and approval by the local Ethics Committee in July 2019 (Ethics Committee Reference: N376). Informed written consent was obtained from the next of kin or legal guardian for each patient enrolled in the study (9).…”
Section: Methodsmentioning
confidence: 99%
“…In our recent study involving children with septic shock, we observed a signi cant reduction in the Vasoactive Inotropic Score (VIS) and Pediatric Logistic Organ Dysfunction (PELOD-2) score at 72 and 96 hours following initiation of CytoSorb therapy, when compared to baseline. Importantly, these reductions were more pronounced in th hemoadsorption group than in a historical cohort of pediatric patients who underwent continuous renal replacement therapy (CRRT) alone (9). Furthermore, we embarked on an exploration of whether the observed hemodynamic improvements were accompanied by corresponding changes in microcirculation during CytoSorb and CRRT therapy in the same cohort of pediatric patients.…”
Section: Introductionmentioning
confidence: 99%